2019
DOI: 10.3390/medicina55070389
|View full text |Cite
|
Sign up to set email alerts
|

A New ABCA3 Gene Mutation c.3445G>A (p.Asp1149Asn) as a Causative Agent of Newborn Lethal Respiratory Distress Syndrome

Abstract: Mutations in adenosine triphosphate-binding cassette transporter A3 (ABCA3) (OMIM: 601615) gene constitute the most frequent genetic cause of severe neonatal respiratory distress syndrome (RDS) and interstitial lung disease (ILD) in children. Interstitial lung disease in children and especially in infants, in contrast to adults, is more likely to appear as a result of developmental deficits or is characterized by genetic aberrations of pulmonary surfactant homeostasis not responding to exogenous surfactant adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Finally, a lung biopsy should be considered in these patients, as it can be of great value in establishing a diagnosis. 23,24 Lung tissue morphology shows suggestive findings such as alveolar septal thickening, alveolar type II cell hyperplasia, and alveolar proteinosis, but does not indicate specific gene defects. In contrast, electron microscopy showed small lamellar dense bodies in all patients in whom it was performed in 2 recent cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a lung biopsy should be considered in these patients, as it can be of great value in establishing a diagnosis. 23,24 Lung tissue morphology shows suggestive findings such as alveolar septal thickening, alveolar type II cell hyperplasia, and alveolar proteinosis, but does not indicate specific gene defects. In contrast, electron microscopy showed small lamellar dense bodies in all patients in whom it was performed in 2 recent cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic protocols with Hydroxychloroquine (HCQ), Corticosteroids and Macrolides in combination are suggested for patients with interstitial lung disease by SP-C deficiency and empirically used in patients with ABCB3 gene mutations [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duration of therapy is not clear in literature and there were reported cases of cure with no recurrences after withdrawal of HCQ in surfactant dysfunction deficiency cases [ 7 , 16 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…(https://www3.cmbi.umcn.nl/hope/ progress/5e9f34796f82a694596d3fa1/). Mitsiakos et al 9 reported a case with a missense variant located in exon 23 of the ABCA3 gene affecting intracellular interactions with total (surfactant) deficiency and fatal early onset. Our patients missense variant located in exon 24 resulted in the substitution of a neutral leucine residue for a non-polar hydrophobic proline residue at position 1226 (p.Leu1226Pro) which can affect intracellular interactions.…”
Section: Discussionmentioning
confidence: 99%